Using DNA barcoding to track seafood mislabeling in Los Angeles restaurants. Issue 5 (10th May 2017) - Willette, Demian A.; Simmonds, Sara E.; Cheng, Samantha H.; Esteves, Sofia; Kane, Tonya L.; Nuetzel, Hayley; Pilaud, Nicholas; Rachmawati, Rita; Barber, Paul H.
Abstract: Seafood mislabeling is common in both domestic and international markets. Studies on seafood fraud often report high rates of mislabeling (e.g., >70%), but these studies have been limited to a single sampling year, which means it is difficult to assess the impact of stricter governmental truth‐in‐labeling regulations. We used DNA barcoding to assess seafood labeling in 26 sushi restaurants in Los Angeles over 4 years. Seafood from 3 high‐end grocery stores were also sampled ( n = 16) in 2014. We ordered 9 common sushi fish from menus, preserved tissue samples in 95% ethanol, extracted the genomic DNA, amplified and sequenced a portion of the mtDNA COI gene, and identified the resulting sequence to known fish sequences from the National Center for Biotechnology Information nucleotide database. We compared DNA results with the U.S. Food and Drug Administration (FDA) list of acceptable market names and retail names. We considered sushi‐sample labels that were inconsistent with FDA names mislabeled. Sushi restaurants had a consistently high percentage of mislabeling (47%; 151 of 323) from 2012 to 2015, yet mislabeling was not homogenous across species. Halibut, red snapper, yellowfin tuna, and yellowtail had consistently high (<77%) occurrences of mislabeling on menus, whereas mislabeling of salmon and mackerel were typically low (>15%). All sampled sushi restaurants had at least one case of mislabeling. Mislabeling of sushi‐grade fish from high‐end grocery stores was also identified in red snapper, yellowfin tuna, and yellowtail, but at a slightly lower frequency (42%) than sushi restaurants. Despite increased regulatory measures and media attention, we found seafood mislabeling continues to be prevalent.